(untitled) (Fourth World Journal, 2024)
This article was originally published in Vol. 9, No. 1, Summer 2010. The study documents the outcomes of a research simulation conducted during a ̈Global Pluralism ̈ course at Antioch University/Muckleshoot College in 2009. During this 10-week exercise, ten graduate students assumed the roles of various stakeholders in climate negotiations, mirroring real-world dynamics observed in international conferences such as the United Nations Framework Convention on Climate Change (UNFCCC). This simulation revealed indigenous peoples’ marginalized status within civil society frameworks.